IMPACT ANALYSIS OF INCOME DIVERSIFICATION ON BANKING PROFITABILITY CASE STUDY OF BANKING IN INDONESIA - Dian Rahmawati; Eugenia Mardanugraha (SEAN Institute, 2023)
Banking is part of the financial system which has an important role to fund economic activities through its intermediary activities. Soundness of banking performance can be seen from the resilience of its capital to absorb risks. Meanwhile, capital is derived from several main components, including profit. In order to increase their capital, banks also make various efforts to increase profitability, including diversification of sources of income, especially from services charge. For this reason, this study examines whether income diversification affects the profit (profitability) of banking. In addition, this study also analyze other factors that affect bank profitability over the period of July 2018 – June 2022. This study uses data off all bank that operating in Indonesia as of June 2022 using generalized method of moment (GMM). The results of the study show that income diversification has a negative impact on banking profitability (ROA and ROE) and there are other variables that have a negative effect, that are third party funds and digital banking services. Meanwhile, credit and GDP growth have a positive effect on profitability. Based on KBMI, income diversification at KBMI 2 and KBMI 3 have a positive effect on profitability. However, KBMI 3 needs to pay attention to the impact of securities and foreign exchange transactions which cause a decrease in profitability. Whereas at KBMI 1, non-interest income has a negative effect and on KBMI 4, there is no significant effect. Meanwhile, other income, which is the main component of non-interest income, has no significant effect on profitability